Environmental Protection or Disguised Protectionism? Reassessing the Necessity Test in Brazil–Retreaded Tyres - Sutrisno, Andri; Priyono, FX. Joko; Trihastuti, Nanik (Jurnal Cakrawala Hukum, 2025)
This article examines the interpretation and application of the necessary criterion under Article XX(b) of the General Agreement on Tariffs and Trade (GATT) 1994 through critical doctrinal analysis of the WTO dispute Brazil–Measures Affecting Imports of Retreaded Tyres (WT/DS332). Employing normative legal research with a case-analytical and comparative approach, the article evaluates Brazil's 2007 import ban on retreaded tyres against the tripartite necessity framework legitimate objective, rational contribution, and the absence of reasonably available less trade-restrictive alternatives and critically interrogates the Appellate Body's application of the chapeau's non-discrimination requirements. The analysis finds that while Brazil's measure provisionally satisfied the Article XX(b) necessity criteria on the merits of its public health and environmental justification, the Appellate Body's chapeau ruling deployed a formalist methodology that conflated discrimination rooted in protectionist intent with discrimination arising from pre-existing regional treaty obligations and domestic judicial intervention beyond governmental control. This article argues that this interpretive approach imposes structurally unrealisable demands upon developing country regulatory actors and produces normatively unjustifiable outcomes. The article advances an original analytical framework for contextually differentiated interpretation of the chapeau, grounded in the Vienna Convention's object-and-purpose mandate, that distinguishes between bad-faith protectionism and institutionally constrained regulatory inconsistency.